Representasi Peran Gender dalam Novel “Perempuan di Titik Nol” Karya Nawal El-Saadawi - Anggi Mesrawati Zebua; Mastawati Ndruru; Noibe Halawa; Yanida Buulolo (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The novel Perempuan di Titik Nol is a literary work that explicitly discusses the issue of gender injustice experienced by women in a patriarchal society. This novel tells the story of Firdaus, a woman who lives in poverty and experiences various forms of oppression, from sexual violence to economic exploitation.This study aims to describe the representation of gender roles and building elements in the novel "Perempuan di Titik Nol". The type of research used is qualitative research with a descriptive approach. The data collection technique used in this study is to observe and record. The data analysis technique used by the researcher uses data collection, data reduction, data display, conclusion drawing and verification (conclusion drawing/verification). Based on the results of the study, there are 5 representations of gender roles in the novel "Perempuan di Titik Nol', namely; marginalization, subordination, stereotypes, violence and workload. From the results of the five representations above, there are several quotes including; marginalization (2 quotes), subordination (2 quotes), stereotypes (3 quotes), violence (3 quotes) and workload (1 quote). With two elements of novel building, namely intrinsic elements and extrinsic elements.